Access to evidence‐based care for eating disorders during the COVID‐19 crisis. Issue 5 (27th April 2020) - Weissman, Ruth S.; Bauer, Stephanie; Thomas, Jennifer J.
Abstract: The COVID‐19 pandemic has forced an abrupt change in the delivery of clinical services, including for individuals with an eating disorder. We present this Virtual Issue as a resource for the eating disorder community to showcase research published in the International Journal of Eating Disorders that provides information on effective strategies to help address the challenges arising from COVID‐19‐related disruptions. Articles included describe original research or systematic reviews on obstacles to health services use and strategies to improve access to care; technological tools to provide or enhance interventions; patients' and clinicians' attitudes or perspectives on using digital tools for clinical care; factors influencing therapeutic alliance; and ideas for improving reach and uptake of digital interventions. We hope that readers will find ways to observe and record their own experiences during this global crisis; the experiences of people at risk for developing or exhibiting an eating disorder; and the experiences of those who care for people with an eating disorder. These lived experiences will be invaluable in formulating hypotheses for future studies in service of advancing the understanding of eating disorders and improving interventions and policies for reducing the burden of suffering attributable to eating disorders.